Defected ground structure-based circularly polarized MIMO filtering dielectric resonator antenna - Xia, Ke; Bao, Yi-Qiang; Zhang, Hai-Feng (Physics letters. A, 2025)
The alumina ceramic is applied to a circularly polarized (CP) filtering dielectric resonator antenna (FDRA) and a multiple-input multiple-output (MIMO) FDRA in this paper. Initially, an optimally performing band-pass filter is engineered and amalgamated with a Wilkinson power divider to establish a filtering feed network. The rectangular dielectric resonator is used as the radiating unit and is excited by the filtering feed network. The proposed CP FDRA demonstrates a relative impedance bandwidth of 37.24 %, a relative axial ratio bandwidth of 32.51 %, a peak gain of 6.08 dBi, and a maximum antenna efficiency of 94.17 %. Subsequently, the single FDRA is expanded into a two-port MIMO antenna. To augment the isolation and CP performance, an innovative defected ground structure is utilized between the dual radiation units. Moreover, the surface current is channeled to fourteen circular copper patches on the back of the substrate via fourteen conductive copper pillars. Following fabrication and soldering, the empirical results corroborate the simulation outcomes. The measured relative impedance bandwidth is 35.83 %, with the maximum isolation reaching 28.23 dB. The proposed MIMO antenna demonstrates exceptional isolation, a broad operating bandwidth, and effective out-of-band rejection, rendering it suitable for integration into the communication infrastructures of fifth-generation and wireless local area networks.